AN ANALYSIS OF CODE-SWITCHING AND CODE-MIXING ON DEDDY CORBUZIER’S PODCAST EPISODE AGNEZ MONICA - Maufi Najmuts Saqib; Widyashanti Anindita (Acceleration: Multidisciplinary Research Journal, 2025)
This paper aims to analyze the types, reasons, and pragmatic function (impact) of code-switching and code-mixing on Dedy Corbusier’s podcast. The data are collected by categorizing the transcript according to the types of code. To validate the data, the researcher used triangulation theory. The result is that the dominant type of code-switching is Intra-sentential, with 50 data (21%) of 235 total data. The submissive type of switching is emblematic with 5 data (5%). The dominant type of code-mixing is intra-sentential, with 68 data (29%). The submissive type of mixing is involving a change of pronunciation with 10 data (4%). The dominant reason is talking about a particular topic, with 111 data (47%) serves a referential pragmatic function, and the submissive of the reason is an expression, with 1 data (0,4%); they rarely discussed group identity. Based on the dominant and submissive reason, Deddy’s Podcast facilitates discussions on specific topics, enhancing clarity and comprehension. This strategic use of language may contribute to the podcast’s widespread appeal, evidenced by its 24.3 million subscribers.